Cumulative post-buckling buckling behavior of smart sandwich structure. Issue 1 (January 2021) - Lal, Achchhe; Markad, Kanif
Abstract: Cumulative post-buckling buckling behavior of smart sandwich structure has been presented with the combination of shape memory alloy (SMA) and shape memory polymer (SMP) in sandwich composite structure under uniform temperature distribution. The analysis is based on higher order shear deformation theory (HSDT) with von Karman nonlinearity by finite element method (FEM). Evaluation of nondimensional critical buckling temperature (NCBT) has been executed under varying plate thickness ratio. Thermal buckling performance of SMA reinforced SMP laminated composites under dynamic temperature condition with different strain rate and variation in SMA volume fraction is also presented first time to understand the cumulative post-buckling behavior.